The Effect of EFL Teachers’ Participation in Professional Development Program on The Change of Their Teaching Behaviour - Sri Kusuma Ningsih (English Education Department at FKIP Nommensen University, 2023)
Professional Development Program (PDP) is essential for effective education, especially for teachers. Teachers' participation in PDP can improve their skills in many aspects, such as instructional strategy practice, performance, and teaching behaviour. This study aimed to determine whether or not there is a significant effect of EFL teachers' participation in PDP on their teaching behaviour. There were 101 EFL teachers who were involved in the study. The data were collected by using Teaching and Learning International Survey (TALIS) questionnaire from Organisation for Economic Co-operation and Development (OECD). This study showed that there is a significant effect of PDP on EFL teachers' teaching behaviour.